EGF‐Loaded Hyaluronic Acid Based Microparticles as Effective Carriers in a Wound Model. (31st March 2017) - Kang, Sun‐Woong; Choi, Jong‐Jin; Kim, Ha‐Na; Seo, Joseph; Park, Soon‐Jung; Kim, Eun‐Young; Park, Se‐Pil; Huh, Kang Moo; Chung, Hyung‐Min; Chung, Ho Yun; Moon, Sung‐Hwan
Abstract : Epidermal growth factor (EGF) is widely recognized to be involved in the regenerative process, but only a few studies document its effect on acute wounds when EGF release is sustained over a period of time by encapsulation in an emulsion‐based hydrogel. Among hydrogels, hyaluronic acid (HA) is a promising carrier because it is biodegradable and known to bind to the components of the Extracellular Matrix (ECM) which undergoes remodeling during regeneration. Coupled with EGF in microparticulates, it may serve to directly deliver the cytokine to the impaired ECM to stimulate cells for ECM remodeling. In this study, a very simple and effective way is demonstrated to produce EGF‐conjugated HA microspheres for the purpose of targeted and sustained EGF delivery to damaged ECM in acute wounds. This approach is advantageous due to its simplicity which may serve to accelerate research in wound regeneration and relevant drug discovery. Abstract : The emulsification of hyaluronic acid (HA) and epidermal growth factor (EGF) produces biodegradable microparticles that are inclined to be immobilized and exhibit monodispersal. This mode of cytokine delivery is advantageous in acute wounds because HA binds to the damaged extracellular matrix, which allows better targeting and a stable dosage over time in comparison to subcutaneous injections.